MEMBANGUN KESADARAN MEREK PADA UMKM SEBAGAI UPAYA MENJAGA EKSISTENSI PRODUK DALAM MASA PANDEMI - Nurulfatmi Azmy (Institut Seni Indonesia Surakarta, 2021)
The spread of Coronavirus 2019 (Covid-19) in all over the world have impacts on culinary business. Some food outlets survive by using the digital transaction method. Moreover, there is a massive number of traditional food production companies that not supported by that kind of technology. Consequently, it may decrease their revenue. This paper focuses in “Kembang Matahari” noodles crackers factory as one of the examples. Even, way before this pandemic era, the factory has been dealing with numerous situations that endangered its identity as a traditional food production company. This article will analyze what circumstances the factory is dealing with since its establishment. The method used to analyze the problem is phenomenology. Therefore, this analysis will be clear from the assumption and groundless pieces of information. This paper will discuss the object in Karl Jasper’s existentialism theory. It will reveal that intersubjective communication between the company and social institution is the key to maintain its existence. This paper aims to inform that interaction opens the door to apply branding awareness.